Peran Inovasi Produk Bank Syariah Indonesia (BSI) dalam Meningkatkan Akses Pemberdayaan UMKM - Dirra Azzuhra; Hartini Hartini; Sismaul Panira; Husni Kamal (Sekolah Tinggi Ilmu Syariah (STIS) Ummul Ayman Pidie Jaya, Ace, 2025)
The Program for Empowerment and Enhancement by Bank Syariah Indonesia (BSI) significantly supports micro, small, and medium enterprises (UMKM) in Indonesia by providing Sharia-compliant financing such as murabahah, as well as fostering product development, digital marketing, and managerial skill enhancement. This initiative improves access to capital, enhances competitiveness, and promotes financial inclusion for UMKM, especially in remote areas. The role of Islamic banking product innovation is crucial in increasing UMKM access to funding, with banks acting as financial facilitators aligned with Sharia principles like mudharabah, musyarakah, and murabahah, which help UMKM obtain capital without interest and through fair systems. The research findings indicate that support through Sharia-based financing mechanisms and digital technology innovations can improve transparency and service accessibility, although challenges such as limited product understanding and administrative barriers still need to be addressed. Bank Syariah Indonesia exemplifies this approach by offering various financing products, training programs, and digital platforms that facilitate UMKM access to capital and markets. These innovations significantly contribute to UMKM empowerment, community welfare, and sustainable national economic growth. The findings demonstrate the potential of these efforts to strengthen financial inclusion and accelerate Sharia-based economic development in Indonesia.